2015
DOI: 10.1645/15-775
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasite Burdens of the Damaraland Mole-Rat (Fukomys damarensis) from Southern Africa

Abstract: Damaraland mole-rats (Fukomys damarensis) of the family Bathyergidae are widely distributed subterranean rodents in sub-Saharan Africa. No parasites have ever been reported for this species and only 1 ectoparasite is described for the entire genus. In the current study ectoparasites were collected from individuals captured at 3 localities in South Africa and Namibia to document the ectoparasite community of F. damarensis, investigate their aggregation patterns and evaluate the influence of season on ectoparasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Thus our data provide evidence for frequency-dependent parasite transmission as would be expected in directly transmitted ectoparasites as those considered in the current study (Côté and Poulin 1995;Rifkin et al 2012;Patterson and Ruckstuhl 2013). Seasonal variation in parasite burden is an ubiqous feature of parasite populations including those of social mammals Ezenwa 2004b;Altizer et al 2006;Huffman et al 2009;Viljoen et al 2011;Cizauskas et al 2015;Klompen et al 2015;Lutermann et al 2015). Consequently, our understanding of the prevalence of density vs. frequency-dependent drivers of host-parasite interactions might be improved by considering seasonal changes in both host and parasite traits.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus our data provide evidence for frequency-dependent parasite transmission as would be expected in directly transmitted ectoparasites as those considered in the current study (Côté and Poulin 1995;Rifkin et al 2012;Patterson and Ruckstuhl 2013). Seasonal variation in parasite burden is an ubiqous feature of parasite populations including those of social mammals Ezenwa 2004b;Altizer et al 2006;Huffman et al 2009;Viljoen et al 2011;Cizauskas et al 2015;Klompen et al 2015;Lutermann et al 2015). Consequently, our understanding of the prevalence of density vs. frequency-dependent drivers of host-parasite interactions might be improved by considering seasonal changes in both host and parasite traits.…”
Section: Discussionsupporting
confidence: 72%
“…However, burrow-dwelling ectoparasites are likely to be less affected by seasonal fluctuations in climate due to the attenuated temperature amplitude and constantly high humidity found in sealed burrow systems (Roper et al 2001;Sumbera et al 2004). Previous work on social bathyergids including the study species have revealed that ectoparasite prevalence and abundance tends to increase during the wet season irrespective of whether they inhabit a summer-or winter-rainfall area (Viljoen et al 2011;Archer et al 2014;Lutermann et al 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Since sample sizes were relatively small for F. kafuensis and F. mechowi (Scharff et al, 1997), it remains unclear whether a similarly great species diversity is more common in the genus Fukomys. However, since the ectoparasite community of Fukomys damarensis Ogilby also showed low parasite abundance but high diversity, this might be a general pattern across members of the genus Fukomys (Lutermann et al, 2015). If ectoparasites, such as mites, would act as intermediate hosts for at least some of the recovered helminth taxa, this could also account for their low prevalence and abundance.…”
mentioning
confidence: 97%
“…As in other subterranean mammals, low species richness of macroparasites is common in bathyergids (Viljoen et al, 2011;Lutermann and Bennett, 2012;Lutermann et al, 2013Lutermann et al, , 2015Archer et al, 2014). Mammalakis macrospiculum has previously only been reported from Bathyergus suillus (Schreber 1782), which occurs sympatrically with our study species in the mesic habitat and this may account for the host sharing (Inglis, 1991;Bennett and Faulkes, 2000;Lutermann and Bennett, 2012).…”
mentioning
confidence: 99%
“…In subterranean hosts, the restrictions of the environment appear to impact on how parasite infections are spread due to limitations on host dispersal (Hafner et al, 2000;Rossin et al, 2010;Archer et al, 2016). Most studies on the parasite fauna of subterranean rodents indicate that parasite diversity is low as a consequence of the restrictive environment of the burrow (Hafner et al, 2000;Rossin and Malizia, 2002;Rossin et al, 2010;Lutermann and Bennett, 2012;Lutermann et al, 2015).…”
mentioning
confidence: 99%